2018
DOI: 10.18865/ed.28.s2.427
|View full text |Cite
|
Sign up to set email alerts
|

A Cross-Site Partnership to Examine Implementation and Sustainability of a School-Based Trauma Program

Abstract: This study contributes to the paucity of empirical information on the organizational factors that influence the implementation of evidence-based mental health interventions in schools. Our findings reveal that different implementation strategies across policies, structures, and resources can result in implementation of a school-based intervention. Frameworks such as Mendel's can be helpful in identifying areas of strength and improvement of implementation within a school organization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…At the community level, cross-sector collaboration based on shared understanding of trauma (e.g., Barto et al, 2018), intra- and inter-organisation partnerships (e.g., Vendetti et al, 2017), and community education (e.g., Ahrens et al, 2022) to ensure shared trauma-informed language, are identified as critical factors. Organisations’ readiness to change (e.g., Winters et al, 2020), vision for trauma-informed approaches (e.g., Popescu et al, 2017), culture (e.g., Unick et al, 2019), climate (e.g., Maltzman et al, 2011), structure (e.g., Vona et al, 2018), and policy landscape (e.g., Winters et al, 2020) influence buy-in, intervention acceptance and sustainability. Leadership commitment (e.g., Atwool et al, 2019; Kim et al, 2021) is also an essential factor, as leaders are important drivers of organisational change.
Figure 1.Determinants of trauma-informed change identified from systematic review.
…”
Section: Resultsmentioning
confidence: 99%
“…At the community level, cross-sector collaboration based on shared understanding of trauma (e.g., Barto et al, 2018), intra- and inter-organisation partnerships (e.g., Vendetti et al, 2017), and community education (e.g., Ahrens et al, 2022) to ensure shared trauma-informed language, are identified as critical factors. Organisations’ readiness to change (e.g., Winters et al, 2020), vision for trauma-informed approaches (e.g., Popescu et al, 2017), culture (e.g., Unick et al, 2019), climate (e.g., Maltzman et al, 2011), structure (e.g., Vona et al, 2018), and policy landscape (e.g., Winters et al, 2020) influence buy-in, intervention acceptance and sustainability. Leadership commitment (e.g., Atwool et al, 2019; Kim et al, 2021) is also an essential factor, as leaders are important drivers of organisational change.
Figure 1.Determinants of trauma-informed change identified from systematic review.
…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, much of the empirical evidence of effective trauma-informed approaches in school-based settings emphasize individual or group intervention programs facilitated by a clinician, such as a psychologist or school social worker (Herrenkohl et al, 2019). Clinician-led models which screen students for acute trauma symptoms and exposure to identify specific interventions for particular students are prevalent (Hoover et al, 2018;Nadeem et al, 2018;Vona et al, 2018).…”
Section: Multi-tiered Systems Of Supportmentioning
confidence: 99%